Critical analysis of the Life Cycle Assessment of the Italian cement industry. (20th May 2017) - Moretti, L.; Caro, S.
Abstract: The interest for environmentally related issues in the construction industry has grown faster in recent years, demonstrating the neccesity to promote both a more responsible use of non-renewable resources and a better use of renewable resources. As a consequence, there is an increasing number of environmental documents and institutional acts on this topic that demonstrate the need for greener approaches in the area of construction engineering. The objective of this study is to evaluate the environmental impact of the Italian gray cement and clinker industry, after distinguishing between the upstream and the core phases of these processes. The study considered clinker and cement generated during 2014 in eleven Italian plants that produced materials complying with the European standard EN 197-1 "Cement - Part 1: Composition, specifications and conformity criteria for common cements". The environmental assessment was conducted through a Life Cycle Analysis (LCA) of these industrial processes, following the standard EN 15804 "Sustainability of construction works, environmental product declarations, core rules for the product category of construction products" and the Product Category Rules (PCR) 2010:09 version 2.1 "Cement". The results permitted to construct the first sector Environmental Product Declaration (EPD) related to cement production published until now by the International EPD System. The analysis of the results demonstrated that among the different phases involved in the production process of these materials (i.e. extraction and production of raw materials and fuels, transportation and core production process), the core phase is responsible for most of the greenhouse emissions (i.e. more than 85% of the total process for clinker, and more than 79% of the total process for cement), and the acidification and eutrophization potential (i.e. 43% and 62% of the total process for clincker, and 33% and 55% of the total process for cement). It was also found that the cement production is mainly responsible for the following environmental impact categories: the overall electrical consumption required as part of these industrial processes (116 kWh/Mg), the output flows of components for re-use and materials for recycling (0.21 and 0.17 kg/Mg, respectively), and the biogenic CO2 emissions (16 kg/Mg). The results highlight the environmental benefits of applying Best Available Techniques (BAT) for this industry, as reported in the European Reference document for the "Production of Cement, Lime and Magnesium Oxide".